2009
DOI: 10.1590/s0100-40422009000300024
|View full text |Cite
|
Sign up to set email alerts
|

Borracha natural e nanocompósitos com argila

Abstract: Recebido em 15/1/09; aceito em 12/3/09; publicado na web em 2/4/09 NATURAL RUBBER AND NANOCOMPOSITES WITH CLAY. The natural rubber is a strategic material which can not be replaced by synthetic rubber in many technological applications. Brazil is a rubber importer, but new techniques of cultivation, breeding and diversification of producing species can reverse this situation. One of the best ways to add value to this commodity is nanotechnology. The production of nanocomposites is already a reality and shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
0
12
0
5
Order By: Relevance
“…Natural rubber (NR) is a bioderived elastomeric polymer which is extensively used for the production of tires, gloves and gaskets (Rippel and Braganç a, 2009;Kohjiya and Ikeda, 2014). It is harvested from the Hevea Brasiliensis tree as a liquid suspension called latex in which the presence of other substances such as proteins, fatty acids, carbohydrates to name a few, make its properties highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…Natural rubber (NR) is a bioderived elastomeric polymer which is extensively used for the production of tires, gloves and gaskets (Rippel and Braganç a, 2009;Kohjiya and Ikeda, 2014). It is harvested from the Hevea Brasiliensis tree as a liquid suspension called latex in which the presence of other substances such as proteins, fatty acids, carbohydrates to name a few, make its properties highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…A borracha natural é um hidrocarboneto cuja fórmu-la química é um polímero de poli(cis-1,4-isopreno) (Rippel & Bragança, 2009). Este hidrocarboneto está presente em mais de 7.500 espécies vegetais, dentre as quais a Hevea brasiliensis (Willd.…”
Section: Introductionunclassified
“…Diferentemente de outros polímeros, a borracha natural apresenta certas características físico-químicas úni-cas, sendo, portanto uma matéria-prima insubstituível para mais de 50 mil produtos industrializados, como pneus, adesivos, couro vegetal, materiais cirúrgicos e uma diversa gama de outros produtos (Rippel & Bragança, 2009).…”
Section: Introductionunclassified
“…Natural rubber is used in a bunch of industrial applications and manufactured products, like tires and gloves, but its presumable biological properties are not explored as it should be. 6 Latex and its constituents have been specifically implicated in multiple biological propertiesand it is known to stimulate angiogenic activity, cell adhesion, extracellular matrix formation, and to improve wound healing in skin tissue. 7,8 Ferreira et al (2009), 9 showed that the non-rubber constituents of H. brasiliensis latex are the bioactive fraction responsible for angiogenic properties of this material.Latexconstituents can be separated in three parts when centrifuged at high speed, consisting of the rubber cream, centrifuged serum (C-serum) and the bottom fraction (B-serum).…”
Section: Introductionmentioning
confidence: 99%